Penerapan Sistem Pendukung Keputusan Pengangkatan Karyawan Tetap Dengan Menggunakan Metode Topsis - Aliy Hafiz (Universitas Mitra Indonesia, 2020)
AbstractDecision support sistems as a computer-based interactive sistem that can help decision unstructured problems.Management of human resources from a company greatly affects many aspects of determining the success of the company's work. From previous research, decision support sistems have been widely applied in various industries to make it easier for management to make decisions.Constraints faced by PT. Tunas Dwipa Matra is a criterion for appointment of employees that has not yet been measured, so that the decision taken is still subjective. The author describes how the process of determining contract employee status is a permanent employee using the Technique For Order of Preference by Simility to of Ideal Solution (TOPSIS) method. The results of this study are decision support sistems that can facilitate the management and determination of contract employees to become permanent employees based on calculation methods.